Income Inequality and Individual Health: Exploring the Association in a Developing Country - Therese Nilsson; Andreas Bergh (Lund University, School of Economics and Management, Department of Economics, 2012)
We use individual and multi-level data from Zambia on child nutritional health to test the absolute income hypothesis (AIH), the relative income hypothesis (RIH) and the income inequality hypothesis (IIH). The results confirm a non-linear positive relation between economic resources and health, confirming the AIH. For the RIH we find sensitivity to what reference group is used. Most interestingly, while the IIH predicts that income inequality, independent from individual income, will affect health negatively, we find higher income inequality to robustly associate with better child health. The results suggest that the relationship between inequality and health in developing contexts might be very different from the predominant view in the existing literature mainly based on developed countries, and that alternative mechanisms might mediate the relationship in poor countries.
Keywords: D31; I14; I15; 330; Income Inequality; Health; Developing Countries